Profiling movie downloaders in Egypt: Law awareness as an attitudinal factor - Elswah, Mona Abdelsattar (AUC Knowledge Fountain, 2016)
This study is aimed at determining the main antecedents of the intention to illegally download movies in Egypt. This study examined the role of law awareness in forming the attitude toward illegal downloading and the methods downloaders use to rationalize their act. A model was proposed based on the planned behavior, neutralization and deterrence theories. A sample of 384 Mass Communication students at Cairo University was surveyed. The findings showed that law awareness does not play a direct role in forming attitudes toward movie illegal downloading. Even though the more illegal downloaders were aware of the illegality of movie copyright infringement, the more they perceived the law as deterrent; they continued downloading movies. The results also indicated that perceived deterrence has no direct correlation with attitude. The results showed that downloaders with lower levels of law awareness needed to rationalize their piracy act, which may indicate that they are aware of the immorality of their act regardless of its illegality. In addition, limiting access to movies and failing to provide more legitimate venues may cause more favorable attitude toward the illegal downloading which may represent one of the very few choices left to movie fans. Furthermore, attitude was found to be the strongest determinant of illegal downloading intention. Moreover, the current findings showed that movie downloaders perceived movie piracy as an easy act. The fight against piracy should include non-downloaders also, since this study showed that the societal acceptance was another driving force for movie piracy.